A new approach to model shale gas production behavior by considering coupled multiple flow mechanisms for multiple fractured horizontal well. (1st February 2019) - Lu, Ting; Liu, Shimin; Li, Zhiping
Highlights: A new shale gas production model accommodating multi-mechanisms is established. Inversion values of parameters match well the data from Barnett shale. Production discrepancy increases with continuous depletion adding multimechanics. Parameters have their own influence period and sensitivity intensity. Abstract: Production decline analysis of multiple fractured horizontal wells (MFHW) is crucial for long-term shale gas development. Analytical solutions of production decline model accounting for sorption, diffusion (slip flow and Knudsen diffusion) and non-static (stress-dependent) permeability can precisely predict the long term production behavior, especially for the late time production period. However, little work has simultaneously incorporated all these mechanisms into production decline analysis for shale gas wells. In this work, a new production decline model for MFHW in shale gas reservoirs incorporating multiple flow mechanisms is established. To weaken the strong nonlinearities of seepage mathematical equation caused by combining multiple mechanisms, perturbation technology is employed to establish the point source solution considering stress-dependent permeability of MFHW and little effort has been done on this before. Besides, Laplace transformation, numerical discrete method, Stehfest numerical inversion algorithm and Gaussian elimination method are employed to solve the new model's mathematical problem. Estimated inversion values of reservoir parameters are consistent with the reported data from Barnett shale. Further, comparisons between production behaviors with and without multimechanics flows were made in three flow periods and the production discrepancy increases with continuous depletion, which is attributed that desorption and diffusion is increasingly important as pressure depleting. Finally, the effects of major parameters on production decline curves are analyzed by using the proposed model and it was found that different parameters have their own influence period and sensitivity intensity.